(untitled) (Research, Society and Development, 2021)
Multiresistant bacteria have been one of the main causes of infection and nosocomial permanence. This is attributed to its ability to acquire resistance to several antibiotics, both through the incorrect use of these drugs and the accommodation to the proposed treatment. Thus, for these bacteria, conventional treatment with antibiotics does not have the potential to eliminate them, so different strategies have been studied, such as the use of natural extracts of medicinal plants. Therefore, keywords such as: natural extracts, antibacterial, Myracrodruon, Myracrodruon urundeuva, Anacardiaceae were used for prospective analysis in the following databases Science direct, PubMed, SciELO, World Intellectual Property Organization (WIPO) and National Institute of Industrial Property (INPI). The results allowed to identify a significant number of scientific articles in relation to the keywords used, emphasizing that there was a difference in the quantity presented by each database due to their particularities regarding their areas of study. From this perspective, Science Direct presented a greater number of findings compared to other databases. Regarding the antibacterial activity of Myracrodruon urundeuva, PubMED demonstrated a better targeting, describing in its records the presence of pharmacological compounds found in plant extracts that configure its effects reported in the literature. With regard to filing patents, the INPI had much lower results in filings than the WIPO, in a global context, China is the country that has filed the most patents so far, followed by South Korea and the USA. The findings point to a lack of technological investments by the Brazilian industry. Even given the low therapeutic applicability of Myracrodruon urundeuva in Brazil, it is still superior to other countries, its main use refers to anti-inflammatory, healing, analgesic and bactericidal activities applied to dentistry. The realization of scientific and technological prospecting is an indispensable tool for the knowledge production chain, being necessary for a better direction of research.